1981
DOI: 10.1093/jn/111.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chronic Ascorbic Acid Deficiency and Excessive Ascorbic Acid Intake on Bile Acid Metabolism and Bile Composition in the Guinea Pig

Abstract: The influence of chronic ascorbic acid (AA) deficiency and excessive ascorbate consumption on bile acid metabolism, liver and plasma cholesterol levels, hepatic microsomal cytochromes and biliary lipid composition was investigated. Male weanling guinea pigs were fed a cereal-based scorbutigenic diet supplemented with four levels of AA for 7 weeks: deficient, 15 and 30 mg/kg; control, 500 mg/kg; and excess, 20,000 mg/kg. Bile acid kinetic parameters were determined following the intraperitoneal administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 50 publications
4
24
1
Order By: Relevance
“…been determined, but a reduction in 7-␣-hydroxylase activity has been demonstrated in vitamin C-deficient guinea pigs (30)(31)(32). Although further investigation is clearly needed, our results re-emphasize the importance of proper vitamin C intake to maintain a plasma lipoprotein profile that is associated with reduced risk for coronary heart disease.…”
Section: Discussionmentioning
confidence: 47%
“…been determined, but a reduction in 7-␣-hydroxylase activity has been demonstrated in vitamin C-deficient guinea pigs (30)(31)(32). Although further investigation is clearly needed, our results re-emphasize the importance of proper vitamin C intake to maintain a plasma lipoprotein profile that is associated with reduced risk for coronary heart disease.…”
Section: Discussionmentioning
confidence: 47%
“…Although the accumulation of TC in serum of ODS-od/od rats fed with a commercial diet was not so much higher than the results of experiments using guinea pigs chronically fed with a vitamin C-deficient diet (15,16), ODS-od/od rats fed with a cholesterol supplied diet resulted in a significant increase of TC in serum and liver. Our result is the same as that of Horio et al using ODS rats fed with a diet supplied 0.5% cholesterol and 0 .25% cholic acid (17).…”
Section: Discussionmentioning
confidence: 62%
“…It was originally believed that vitamin C's cholesterol lowering effects was due to its role as a cofactor for the enzyme 7-alphahydroxylase, the rate limiting enzyme in the transformation of cholesterol to bile acids. 66 However this hypothesis has been disconfirmed in subsequent research which showed that plasma vitamin C concentrations had no effect on the rates of bile acid production in the liver. 53,67 Therefore vitamin C might play out its role in the mechanisms responsible for the removal of cholesterol from the blood.…”
Section: Discussionmentioning
confidence: 99%